2014
DOI: 10.1038/ncomms6685
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic catenation is monitored and resolved by a PKCε-regulated pathway

Abstract: Exit from mitosis is controlled by silencing of the spindle assembly checkpoint (SAC). It is important that preceding exit, all sister chromatid pairs are correctly bioriented, and that residual catenation is resolved, permitting complete sister chromatid separation in the ensuing anaphase. Here we determine that the metaphase response to catenation in mammalian cells operates through PKCε. The PKCε-controlled pathway regulates exit from the SAC only when mitotic cells are challenged by retained catenation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
46
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 67 publications
(109 reference statements)
3
46
0
Order By: Relevance
“…The processive changes the cell is undergoing at this time is consistent with the hypothesis that S227 phosphorylation induces a switch in substrate selection that would be required during these transitions. We and others2028 have demonstrated that some tumour-derived cell models have a defective G2 catenation checkpoint, meaning that they are more likely to enter mitosis with residual catenation resulting in an increase in the number of chromatin bridges as they traverse metaphase and anaphase. We see evidence of this in the Aurora B S227A mutant cells as the presence of PICH-positive structures in anaphase (Pike, unpublished observations) increasing the likelihood of residual DNA in the cytokinetic furrow, as well as the observed increase in cells attempting to undergo cytokinesis after PKCɛ inhibition or Aurora B S227A expression with Lap2β-positive chromatin bridges we report here.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The processive changes the cell is undergoing at this time is consistent with the hypothesis that S227 phosphorylation induces a switch in substrate selection that would be required during these transitions. We and others2028 have demonstrated that some tumour-derived cell models have a defective G2 catenation checkpoint, meaning that they are more likely to enter mitosis with residual catenation resulting in an increase in the number of chromatin bridges as they traverse metaphase and anaphase. We see evidence of this in the Aurora B S227A mutant cells as the presence of PICH-positive structures in anaphase (Pike, unpublished observations) increasing the likelihood of residual DNA in the cytokinetic furrow, as well as the observed increase in cells attempting to undergo cytokinesis after PKCɛ inhibition or Aurora B S227A expression with Lap2β-positive chromatin bridges we report here.…”
Section: Discussionmentioning
confidence: 84%
“…This may be because the cells fail to complete cytokinesis due to an inability to resolve the trapped DNA and/or failure to exit the checkpoint. We have demonstrated previously a critical role for PKCɛ in the response to metaphase catenation20. The inhibition of PKCɛ activity during the metaphase–anaphase transition leads to an increase in the number of anaphase ultra-fine bridges that persist through to cytokinesis, activating the abscission checkpoint.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Given the known interaction of condensin II with MCPH1 14,15 , the occurrence of unresolved sister chromatids 10 and the extended prometaphase reported here for human cells lacking MCPH1 function, it is interesting to consider that altered decatenation activity during mitosis directly contributes to the occurrence of MCPH1 primary microcephaly. The slight increase in the number of segregation errors observed during anaphase provides additional support to this scenario, as incomplete decatenation is one of the main mechanisms underlying lagging or bridged chromosomes 2729 .…”
Section: Discussionmentioning
confidence: 85%
“…Control siRNA (5Ј-UUCUCCGAACGUGUCACGUTT-3Ј), siJMJD5-2 (5Ј-CCAGAUGUGAAGUUAGAAATT-3Ј), and Mad2 SMART pool (5Ј-GAAAGAUGGCAGUUUGAUA-3Ј, 5Ј-UAAAUAAUGUGGUGGAACA-3Ј, 5Ј-GAAAUCCGUU-CAGUGAUCA-3Ј, and 5Ј-UUACUCGAGUGCAGAAAUA-3Ј) (21) were synthesized by GenePharma (Shanghai, China). The siJMJD5-1 (sc-75359) and JMJD5 CRISPR/Cas9 KO Plasmid (sc-405787) were purchased from Santa Cruz Biotechnology.…”
mentioning
confidence: 99%